Students Perceptions of the Use of Technological Media in Strengthening Arabic Reading Skills - Nanda Dzikrillah Pelealu; Umi Machmudah; Ma'rifatul Munjiah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
The purpose of this study is to explore the perceptions of 8th grade students at Muhammadiyah Junior High School Bantul, Yogyakarta regarding the use of technological media in Arabic language instruction, with a particular focus on reading skills. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation, and analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that the majority of students hold a positive perception of the use of technological media, as it is considered to facilitate vocabulary comprehension, enhance learning motivation, and create a more interactive and engaging learning atmosphere. Individual factors, the characteristics of the media, and the learning context also contribute to shaping these perceptions. This study provides practical contributions to the development of Arabic language learning strategies that are relevant to the characteristics of the digital generation and can serve as a reference for teachers and educational institutions in optimizing technological media to improve reading skills.